Mujeres tras las cámaras en el documental latinoamericano. Conclusiones de un estudio transversal de la evolución histórica - Dr. Pablo CALVO DE CASTRO (Fonseca, Journal of Communication, 2023)
This article discusses the contributions of the woman film directors in the context of the Latin-American production. The starting point is based on an inequality position regarding the achievements of men and their preeminence in a sector which belongs to a social frame characterized by a structural machismo